Evaluation of cerebral venous thrombosis secondary to oral contraceptive use in adolescents - Ozdemir, Hasan H.; Varol, Sefer; Akil, Esref; Acar, Abdullah; Demir, Caner F. (Springer-Verlag Italia Srl, 2015)
Our goal was to evaluate the clinical patterns, additional risk factors, treatment and outcome of cerebral venous thrombosis (CVT) related to adolescent oral contraceptive pill (OCP) usage. We evaluated 22 patients with CVT related to OCPs admitted to Firat and Dicle University Hospitals from January 2008 to January 2013. We assessed the clinical features, risk factors, imaging results and prognosis. Magnetic resonance imaging (MRI) and magnetic resonance were the preferred procedures for the diagnosis of CVT. MRI revealed parenchymal lesions in 11 (50 %) patients, and the remaining patients had normal MRIs. The sinuses most frequently affected by thrombosis were the superior sagittal sinus and the transverse sinus. The additional risk factors identified for CVT were antiphospholipid syndrome, protein C deficiency, protein C and S deficiency, factor V Leiden associated with heterozygous antithrombin III deficiency, methylenetetrahydrofolate reductase and prothrombin gene mutations. CVT may be overlooked in adolescents because it is more common among middle-aged and elderly adults. CVT should be suspected in the presence of neurological symptoms in adolescents, especially in those using OCPs.
Keywords: Adolescents; Cerebral venous thrombosis; Oral contraceptives